2022
DOI: 10.3390/plants11020199
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Physiological Regulation of Aspartic Acid-Mediated Enhancement of Heat Stress Tolerance in Perennial Ryegrass

Abstract: Aspartate is the most critical amino acid in the aspartate metabolic pathway, which is associated with multiple metabolic pathways, such as protein synthesis, nucleotide metabolism, TCA cycle, glycolysis, and hormone biosynthesis. Aspartate also plays an important role in plant resistance to abiotic stress, such as cold stress, drought stress, salt stress or heavy metal stress. This study found that the chlorophyll content and antioxidant active enzyme content (SOD, CAT, POD and APX) of perennial ryegrass trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Our study found that foliar application of amino acids (Asp) can affect plant vegetative development and improve plant growth under salt stress. Moreover, aspartic acid enhanced the heat tolerance of perennial ryegrass ( Lei et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that foliar application of amino acids (Asp) can affect plant vegetative development and improve plant growth under salt stress. Moreover, aspartic acid enhanced the heat tolerance of perennial ryegrass ( Lei et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under salt stress, Asp accumulates with other amino acids like proline, which is linked to its involvement in osmotic adjustment and membrane stability ( Hayat et al., 2012 ). Although the underlying metabolic pathways are unknown, exogenous application of Asp can improve plant tolerance to salt ( Zhang et al., 2020 ), heat stress ( Lei et al., 2022 ), and cadmium toxicity ( Rizwan et al., 2017b ) based on plant growth and physiological responses. In plants, vascular tissues are responsible for transporting wide-ranging types of amino acids with varying concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The plant metabolic network has to be reprogrammed under stresses so that essential metabolic homeostasis is maintained and protective metabolites are produced to enhance stress tolerance [ 21 ]. Exogenous application of metabolites, such as amino acids, sugars, and specialized metabolites (secondary metabolites), has proven to effectively increase stress tolerance in various crop plants [ 17 , 22 , 23 , 24 ]. Evolving metabolomics approaches have shed light on the regulation of central metabolism and specialized metabolism under abiotic stresses [ 1 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other amino acids, including valine and β-alanine, were largely accumulated in ARs from ECH. This was because amino acids in the aspartate–glutamate pathway are commonly used as nitrogen carriers and are converted into other amino acids, such as valine, threonine, and isoleucine . We speculated that the large amount of amino acids in the aspartate–glutamate pathway was consumed for adaptation to the heap-cultivation conditions, resulting in the utilization of these amino acids for the synthesis of other amino acids, such as valine and β-alanine.…”
Section: Resultsmentioning
confidence: 99%